Pharmacokinetic Properties of 2nd-Generation Fibroblast Growth Factor-1 Mutants for Therapeutic Application - Xia, Xue; Babcock, Joseph P.; Blaber, Sachiko I.; Harper, Kathleen M.; Blaber, Michael (PLOS ONE, 2012)
Fibroblast growth factor-1 (FGF-1) is an angiogenic factor with therapeutic potential for the treatment of ischemic disease. FGF-1 has low intrinsic thermostability and is characteristically formulated with heparin as a stabilizing agent. Heparin, however, adds a number of undesirable properties that negatively impact safety and cost. Mutations that increase the thermostability of FGF-1 may obviate the need for heparin in formulation and may prove to be useful “2nd-generation” forms for therapeutic use. We report a pharmacokinetic (PK) study in rabbits of human FGF-1 in the presence and absence of heparin, as well as three mutant forms having differential effects upon thermostability, buried reactive thiols, and heparin affinity. The results support the hypothesis that heparan sulfate proteoglycan (HSPG) in the vasculature of liver, kidney and spleen serves as the principle peripheral compartment in the distribution kinetics. The addition of heparin to FGF-1 is shown to increase endocrine-like properties of distribution. Mutant forms of FGF-1 that enhance thermostability or eliminate buried reactive thiols demonstrate a shorter distribution half-life, a longer elimination half-life, and a longer mean residence time (MRT) in comparison to wild-type FGF-1. The results show how such mutations can produce useful 2nd-generation forms with tailored PK profiles for specific therapeutic application.